The impact of the learning cycle on the achievement of the third intermediate grade students in Arabic grammar and memorization (Journal of the College of Basic Education, 2022)
The research aims to know the effect of the learning cycle on the achievement and retention of the third intermediate grade students in Arabic grammar. This is done by verifying the following two zero hypotheses:- (There is no statistically significant difference at the level (0.05) between the average achievement of students who study Arabic grammar using the learning cycle and the average achievement of students who study Arabic grammar in the usual (inductive) way in the post-test).- (There is no statistically significant difference at the level (0.05) between the average achievement of students who study Arabic grammar using the learning cycle and the average achievement of students who study Arabic grammar in the usual (inductive) way in choosing retention).